2003
DOI: 10.1038/nature02197
|View full text |Cite
|
Sign up to set email alerts
|

Structural snapshots of the mechanism and inhibition of a guanine nucleotide exchange factor

Abstract: Small GTP-binding (G) proteins are activated by GDP/GTP nucleotide exchange stimulated by guanine nucleotide exchange factors (GEFs). Nucleotide dissociation from small G protein-GEF complexes involves transient GDP-bound intermediates whose structures have never been described. In the case of Arf proteins, small G proteins that regulate membrane traffic in eukaryotic cells, such intermediates can be trapped either by the natural inhibitor brefeldin A or by charge reversal at the catalytic glutamate of the Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
357
1
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 300 publications
(374 citation statements)
references
References 43 publications
8
357
1
8
Order By: Relevance
“…Communication between the membrane and the GEF domain involves little direct contact, if any, and can thus be described in the framework of allostery. It is well established that Sec7 domains have little conformational flexibility, 26,27,[29][30][31][32][33] which makes it unlikely that the GEF activity is regulated by conformational changes at the level of the Sec7 domain. In the following sections, we discuss our current knowledge on the regulatory roles of non-catalytic domains of eukaryotic and bacterial ArfGEFs at the membrane interface.…”
Section: The Allosteric Contribution Of Membranes To the Activation Omentioning
confidence: 99%
See 1 more Smart Citation
“…Communication between the membrane and the GEF domain involves little direct contact, if any, and can thus be described in the framework of allostery. It is well established that Sec7 domains have little conformational flexibility, 26,27,[29][30][31][32][33] which makes it unlikely that the GEF activity is regulated by conformational changes at the level of the Sec7 domain. In the following sections, we discuss our current knowledge on the regulatory roles of non-catalytic domains of eukaryotic and bacterial ArfGEFs at the membrane interface.…”
Section: The Allosteric Contribution Of Membranes To the Activation Omentioning
confidence: 99%
“…2C). Crystallographic analysis of Arf/ArfGEF intermediates captured by the drug BFA, 26,27 by a mutation of catalytic glutamate that occupies the Mg 2C binding site 26,28,29 and by removal of GDP 14 revealed that ArfGEFs activate membrane-associated Arf-GDP in 2 discrete steps (Fig. 2C).…”
Section: The Allosteric Contribution Of Membranes To the Activation Omentioning
confidence: 99%
“…One such mutation in yeast Gea1p, M699L, was able to confer resistance to BFA both in vivo and in vitro (Peyroche et al, 1999). The crystal structures of the Sec7 domain-Arf1-GDP-BFA complex have shown that M699 in Gea1 (corresponding to M832L in GBF1) makes a direct van der Waals contact with the BFA molecule in the complex (Mossessova et al, 2003;Renault et al, 2003). We introduced the corresponding mutation, M832L, into YFP-GBF1.…”
Section: Mechanism Of Bfa-induced Stabilization Of Gbf1 On Membranesmentioning
confidence: 99%
“…Precedent for this approach emerges from the observation that the natural product Brefeldin A (BFA) binds to a related small GTPase, Arf, and its exchange factor, ARNO. 9 In this complex, GDP is also present, resulting in a quaternary complex where BFA is located in a hydrophobic pocket at the Arf-ARNO interface, onethird of which is contributed by ARNO and two-thirds by Arf. BFA acts as an uncompetitive inhibitor that stabilises an abortive Arf-GDP-ARNO complex resulting in inhibition of the secretory pathway in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%